A decline in avian cytokine expression with age revealed by commercially available cytokine array - Levkovich, Guy; Almagor, Dana; Saibaba, Ganesan; Bendikov-Bar, Inna; Rusal, Mark; Lokshtanov, Dmitri; Shinder, Dmitri; Sagi, Dror (Frontiers in Physiology, 2023)
Cytokines are secreted immunomodulators that are key regulators of the avian immune response. Currently, the most commonly used method to follow cytokine expression is qPCR, which measures cellular levels of mRNA, rather their extracellular circulating levels. Here we present a commercially available cytokine array designed to assay circulating expression levels of multiple cytokines and immunomodulators simultaneously. Upon minor modifications to the manufacturer protocol, background noise was reduced, leading to a significant increase in the sensitivity of the device. Our data indicate that the array is reliable and produce consistent data between biological repeats. We tested the reproducibility of the array in a biologically relevant context by assessing age-related changes in circulating cytokines. While individual features did not show a consistent pattern, our data revealed a consistent decline in the median of all cytokine values, supporting the validity of the array in studying biological processes.